The Effect of A Proposed Educational Design Based on The Nardo Model on Motor Linking Ability In Artistic Gymnastics (Journal of the College of Basic Education, 2025)
The research efforts were represented in the low ability to limit the motor and the whole in the junior gymnastics team, so the researchers resorted to adding an alternative through the use of an educational model that can help in reducing this problem, which is the Nardo model, which may have a positive effect on the ability to decline motor in artistic gymnastics. , as the sample does not include (14) player. They are the Iraqi national team player for Nanin, the experimental application was used in the manner of two equal groups to suit the nature of the research problem, and the two wonderful researchers succeeded in experimenting with the research in the experimental group and through the results the researchers reached the proposed program that agreed with the Nadro model that had a great impact in developing the ability of motor cooperation among the experimental research technician. And he mastered the control of the Nadro model research in learning different sports activities and the necessity of introducing the Nadro model among the methods used in learning for other age groups.